(untitled) (CIPEEX, 2022)
With the advent of postmodernism, renewable energy sources gained more strength. Postmodernism emerged between 1968 and 1972, and now all constructions seek a reason, there is nothing absolute anymore, so there is no longer a need to use only non-renewable sources, as postmodernism brought an idea of deconstruction. Foucault believes that a more viable and sustainable production is not something sedentary, but nomadic, that is, it undergoes changes seeking improvements (HARVEY, 2004). The new technologies that emerge daily require more and more energy, however, planet Earth is going through a complicated period called global warming, that is, it can no longer support such carbon dioxide emissions and such waste of its resources. The most plausible solution would be to produce energy using fewer natural resources and releasing fewer pollutants into the atmosphere. Strategies and projects that encourage energy conservation, waste reduction, and the reduction of greenhouse gas emissions are being employed in various countries. Two examples are the United States and the members of the European Union. The United States, during the oil supply crisis in 1970, formulated its first efficiency standards (DIXON, 2010). In the same period, the European Union created legal instruments aimed at reducing energy demand and pollutant emissions (FOUQUET, 2013). Clean energy is derived from natural resources that are replenished on a larger scale than they are consumed, for example: there is more sunlight entering the planet than mankind will ever be able to use. However, they produce much fewer problems for nature compared to non-renewables, as when fossil fuel is burned to produce energy, it causes a large and dangerous emission of carbon dioxide. Renewables also produce this harmful gas, but at a much lower level, making them useful in the fight against the climate crisis the world is facing. Until now, the renewable sources are: biomass, wind, hydro, ocean (tidal), geothermal, green hydrogen, and solar (NADARAJAH et al., 2016). Countries like Brazil, the United States, and the European Union bloc have devised paths to meet this domestic demand. The Ministry of Mines and Energy has composed two long-term projects, called the National Energy Plan – PNE 2030 and 2050. The second aims for a Brazilian energy matrix with over 50% renewable sources. (JANNUZZI, 2005). The United States has a clean energy plan. This aims to boost the production of clean energy from wind and solar sources, with the goal of promoting better sustainability for the country. The U.S. Department of Energy is working to promote the efficiency of new energy projects in areas with the goal of expanding the production of solar energy, onshore wind energy, and geothermal energy. The goal for solar aims to increase the generation of solar energy delivered in the country from the current 4% to 40% by 2035 and to 45% by 2050 . The challenges that the European Union (EU) faces in the energy sector include issues such as the increasing dependence on imports and the growing global energy demand. The EU’s goal is to achieve the target of 20% energy efficiency by 2020, but a new update extended the deadline to 2030 and set the percentage at 32.5% for the increase of renewable sources in the energy mix of the countries in this bloc . The focus of this is solar energy, as among the various other renewable energy sources, it is the most promising and freely available energy source. The world’s main energy source, oil, besides being a fossil fuel highly harmful to the ozone layer, is limited and expensive, and the other sources are still far from becoming as efficient and economically viable as solar energy has already become. Therefore, the sun is a great "tool" to develop the economic status of emerging countries and to bring dignity to disadvantaged people. According to the table, all renewable sources are in full development and expansion worldwide. Solar energy (yellow) is falling behind only hydroelectric (blue). In 2000, the world produced 1228 MW, in 2021 the world produced 854795 MW, so there was an increase of approximately 69000%. China is currently leading the annual production ranking with a capacity of 253.4 GW. In 2020, Brazil ranked ninth among the countries that increased their capacity the most within their territory, with an increase of 3.1 GW in capacity in that year alone. Taking advantage of government programs, the Evangelical University of Goiás – UniEvangélica, partnered with the company ENEL Brazil. In this project, a parking lot containing 2,900 solar panels was built, generating an annual savings of approximately 2,400 MWh. This solar parking lot supplies 60% of all the energy that Unievangélica demands. The general objective of this work was to analyze, based on bibliographic and documentary research, the main concepts, definitions, and approaches related to energy efficiency. The studies are based on international and Brazilian projects and public policies on the subject. Thus, based on these studies, they aim to construct ideal scenarios, keywords, and analyses of historical and contemporary contexts related to renewable energy production and its relationship with global issues such as climate change and global warming.